Assessment of the dynamic structural behaviour of footbridges based on experimental monitoring and numerical analysis - DEBONA,G. L. (2020)
Abstract This research work aims to investigate the dynamic structural behaviour and assess the human comfort of footbridges, when subjected to pedestrian walking, based on experimental tests and tuning of finite element model. Therefore, the investigated structure is associated to a real pedestrian footbridge, spanning 24.4m, located at the campus of the State University of Rio de Janeiro (UERJ), Rio de Janeiro, Brazil. Initially, an experimental modal testing was conducted using two data acquisition strategies. After that the experimental forced vibration tests were performed on the footbridge, considering the pedestrians walking with different step frequencies. In sequence of the study, a finite element model was developed based on the ANSYS computational program. The experimental footbridge tests were used for the calibration of results on the numerical model. Finally, a human comfort assessment was performed, based on the comparisons between the results (peak accelerations), of the dynamic experimental monitoring and the recommendations provided by design guides SÉTRA, HIVOSS and AISC.